Krizės mums leido daryti dalykus, kuriuos buvome numatę Vyriausybės programoje. Interviu su Ingrida Šimonyte - Vilpišauskas , Ramūnas (Politologija, 2025)
Interview conducted by Ramūnas Vilpišauskas on January 16, 2025, in Vilnius. Transcribed by Justė Giedraitytė. Interview was edited for brevity and clarity.